Design and Implementation of a Web-Based RT/RW Service Information System and Resident Data Monitoring at Mekarsari Village Environment - Muhamad Alfay Rauf (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This study aims to design and implement a web-based RT/RW service information and resident data monitoring system to improve the effectiveness, accuracy, and transparency of community services. RT/RW administrative services at Mekarsari Village area consist of 28 Neighborhood Associations (RT), 10 Community Associations (RW), and 5,842 residents. Currently, Mekarsari Village still uses a manual services system, which causes several problems such as delays in processing, data recording errors, and difficulties in monitoring resident data collection. The methodology used in this research is the Agile method, which includes an iterative and adaptive process to user needs. Each iteration involves planning, design, implementation, testing, and direct evaluation by users. The technologies used in the design and implementation of this system include the CodeIgniter framework for the backend, MySql as database, and Bootstrap for the user interface. The research data was obtained from direct observation and interviews with village officials, RT/RW, and local residents.